2012
DOI: 10.1089/met.2012.0043
|View full text |Cite
|
Sign up to set email alerts
|

Screening Cognition in the Elderly with Metabolic Syndrome

Abstract: We found that subjects with metabolic syndrome have lower MMSE scores than those without, even without symptomatic cognitive impairment, and that the number of metabolic abnormalities is independently associated to lower MMSE scores. We suggest that these patients should always undergo cognitive screening to prevent more severe outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
2
22
1
Order By: Relevance
“…The current investigation of the individual MetS components identified a cross‐sectional association between high blood pressure and better performance on sustained attention, episodic memory, and global cognition at baseline. This conflicts with other studies that have reported a greater risk of cognitive impairment in individuals with hypertension, although age may be an effect modifier, because these studies were conducted in younger populations. A study examining blood pressure and cognitive function over a wide age range found high blood pressure to be associated with greater risk of cognitive impairment in individuals younger than 75, but high blood pressure was associated with better cognitive function in older participants, and this association was strongest in those aged 85 and older .…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…The current investigation of the individual MetS components identified a cross‐sectional association between high blood pressure and better performance on sustained attention, episodic memory, and global cognition at baseline. This conflicts with other studies that have reported a greater risk of cognitive impairment in individuals with hypertension, although age may be an effect modifier, because these studies were conducted in younger populations. A study examining blood pressure and cognitive function over a wide age range found high blood pressure to be associated with greater risk of cognitive impairment in individuals younger than 75, but high blood pressure was associated with better cognitive function in older participants, and this association was strongest in those aged 85 and older .…”
Section: Discussioncontrasting
confidence: 91%
“…There was a high prevalence of high blood pressure according to the NCEP ATP III criteria in this cohort (94.4%), which demonstrates the difficulty in discriminating between individuals when applying the current definition of MetS to this age group, but modifying criteria to use less‐strict cutoffs did not change the results. In contrast, low HDL‐C was associated with lower MMSE scores at baseline, consistent with previous studies that have reported that lower HDL‐C is associated with greater risk of cognitive impairment . The Leiden 85+ Study found an association between low HDL‐C and lower baseline MMSE scores but, similar to the current study, did not find a longitudinal effect…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Many recent studies have reported that unhealthy lifestyle behaviours and cardio-metabolic risk factors (eg, metabolic syndrome and cardiovascular diseases) are positively associated with cognitive impairment (Komulainen et al, 2007;Liu et al, 2013;Parnowski & Kaluza, 2013;Viscogliosi et al, 2012) and dementia (eg, Alzheimer's disease) (Hildreth, Grigsby, Bryant, Wolfe, & Baxter, 2014). Elderly individuals with metabolic syndrome show a higher prevalence of cognitive impairment than do those without metabolic syndrome (Panza et al, 2011).…”
mentioning
confidence: 99%